Peningkatan Kesadaran Berkonstitusi Melalui Penerapan Metode Role Playing dalam Mata Pelajaran PPKN di MTsN 4 Gunungkidul - Ani Susilawati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2017)
This research aims to increase awareness of constitutional process grade VIII A MTs N 4 year Challenging lessons 2017/2018 using Role Playing. As for the hypothesis of research this is a class act: a learning method using Role Playing can raise awareness of the law students of class VIII A Basic competence in finding out the meaning, the position and the function of the Constitution of the unitary State of the Republic of Indonesia the year 1945, as well as other legal regulations in the national legal system in the country 4 MTs Gunungkidul. During the learning process, made observations on the performance of the teacher as researcher and conducted an assessment of cognitive and affective student through daily observation sheets and Deuteronomy. Other findings during the study discussed among researchers with the observer was equipped with the data the results of observations made reflection on each cycle. The results of the research on cycle I and cycle II shows that there is an increased awareness of constitutional process students assuming the results of student learning increased then the constitutional process awareness has also increased. The results of the assessment of student learning outcomes are: cycle I: observational stance of students demonstrating achievement of 70.84% with thorough criteria of good and cognitive value of reached 78.13% with good criteria. Cycle II: results of a observation attitude reached 77.08% with thorough the criteria of good and cognitive value of reached 93.75% criteria very well. Keywords: Awareness of The Constitutional Process, Role Playing Abstrak Penelitian ini bertujuan untuk meningkatkan kesadaran berkonstitusi siswa kelas VIII A MTs N 4 Gunungkidul tahun pelajaran 2017/2018 dengan menggunakan metode Role Playing. Adapun hipotesis penelitian tindakan kelas ini adalah pembelajaran menggunakan metode Role Playing dapat meningkatkan kesadaran hukum siswa kelas VIII A pada kompetensi Dasar menelaah makna,kedudukan dan fungsi Undang-Undang Dasar Negara Kesatuan Republik Indonesia Tahun 1945, serta peraturan hukum lainnya dalam sistem hukum nasional di MTs Negeri 4 Gunungkidul. Selama proses pembelajaran, dilakukan pengamatan terhadap kinerja guru sebagai peneliti dan dilakukan penilaian kognitif dan afektif siswa melalui lembar observasi dan ulangan harian. Temuan lain selama berlangsungnya pembelajaran didiskusikan antara peneliti dengan observer dilengkapi dengan data hasil pengamatan yang dilakukan refleksi pada setiap siklusnya. Hasil Penelitian pada siklus I dan siklus II menunjukkan adanya peningkatan kesadaran berkonstitusi siswa dengan asumsi hasil belajar siswa meningkat maka kesadaran berkonstitusi juga meningkat. Hasil Penilaian terhadap hasil belajar siswa adalah: siklus I: observasi sikap siswa menunjukkan pencapaian 70,84% dengan kriteria baik dan ketuntasan nilai kognitif mencapai 78.13% dengan kriteria baik. Siklus II: hasil observasi sikap mencapai 77,08% dengan kriteria baik dan ketuntasan nilai kognitif mencapai 93,75% dengan kriteria sangat baik. Kata Kunci: Kesadaran berkonstitusi, Role Playing